Slow deep breathing and guided imagery therapy as a nonpharmacological treatment for patients with anxiety - Fina Listiani; Yanuar Fahrizal (JOURNAL OF Mental Health Concerns, 2026)
Background: Anxiety is one of the most prevalent mental health problems worldwide and can significantly impair an individual’s daily functioning if not properly managed. Non-pharmacological interventions are increasingly preferred due to their safety, ease of application, and minimal side effects. Purpose: To analyze the effectiveness of a combination of slow deep breathing and guided imagery in reducing anxiety levels in patients. Method: A case study approach in psychiatric nursing care involving a patient with clinically significant anxiety. Data were collected through interviews, observations, and the Hospital Anxiety and Depression Scale (HADS) as a standardized assessment tool. The intervention consisted of a combination of slow deep breathing and guided imagery conducted for 7 consecutive days, with each session lasting 10–15 minutes. Results: The results showed a reduction in the patient’s anxiety score from 11 (abnormal category) before the intervention to 6 (normal category) after the intervention. The patient also demonstrated decreased restlessness, improved relaxation ability, and better control of negative thoughts following the combined intervention. Conclusion: The combination of slow deep breathing and guided imagery was effective in reducing anxiety by addressing both physiological and psychological responses. This intervention can be considered an effective non-pharmacological nursing strategy to improve emotional well-being and coping mechanisms in patients with anxiety. Keywords: Anxiety; Guided Imagery; Nursing Care; Relaxation Therapy; Slow Deep Breathing.